2023
DOI: 10.3390/plants13010011
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of Catalase Gene Families in Triticeae

Mouna Ghorbel,
Ikram Zribi,
Najla Haddaji
et al.

Abstract: Aerobic metabolism in plants results in the production of hydrogen peroxide (H2O2), a significant and comparatively stable non-radical reactive oxygen species (ROS). H2O2 is a signaling molecule that regulates particular physiological and biological processes (the cell cycle, photosynthesis, plant growth and development, and plant responses to environmental challenges) at low concentrations. Plants may experience oxidative stress and ultimately die from cell death if excess H2O2 builds up. Triticum dicoccoides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 96 publications
1
0
0
Order By: Relevance
“…metal toxicity, which was consistent with the stress-responsive cis-regulatory elements identified in the promoter region of TmMnSOD [39]. Accumulated experimental data indicated that at the transcriptional level, most of the antioxidant genes exhibited high plasticity and complex regulatory features, allowing the plants to properly respond and precisely activate their antioxidant defense system [40][41][42].…”
Section: Effect Of Cytokinin Priming and Subsequent Uv-b Treatment On...supporting
confidence: 78%
“…metal toxicity, which was consistent with the stress-responsive cis-regulatory elements identified in the promoter region of TmMnSOD [39]. Accumulated experimental data indicated that at the transcriptional level, most of the antioxidant genes exhibited high plasticity and complex regulatory features, allowing the plants to properly respond and precisely activate their antioxidant defense system [40][41][42].…”
Section: Effect Of Cytokinin Priming and Subsequent Uv-b Treatment On...supporting
confidence: 78%